Liquidity premia and interest rate parity - Linnemann, Ludger; Schabert, Andreas (Technische Universität Dortmund, 2013)
Risk-free assets denominated in US currency not only offer a pecuniary return, but also provide transactions services, both nationally and internationally. Accordingly, the responses of bilateral US dollar exchange rates to interest rate shocks should differ substantially with respect to the (US or foreign) origin of the shock. We demonstrate this empirically and apply a model of liquidity premia on US treasuries originating from monetary policy implementation. The liquidity premium leads to a modi fication of uncovered interest rate parity (UIP), which is able to explain observed deviations of exchange rate dynamics from UIP predictions. In line with empirical evidence, the model predicts an appreciation of the US dollar subsequent to an increase in US interest rates as well as in SOE interest rates.
Discussion Paper / SFB 823;43/2013
Keywords: exchange rate dynamics; liquidity premia; monetary policy shocks; uncovered interest rate parity; 310; 330; 620